SLOPE STABILITY ANALYSIS ON THE EASTERN PIT LOWWALL PT XYZ IN SOUTH KALIMANTAN - Satria Adhi Jatikusum, Muhammad
PT XYZ in the province of South Kalimantan is facing geotechnical problem during the mining process between January - June 2019 in the Eastern Pit. At the surface behind the crest of the lowwall slope, two tensile cracks were formed with a length of about 250 meters each. The tensile cracks are estimated to be formed between March - June 2019 at an elevation of RL 60 and predicted as preliminary sign of plane failure. For this reason, slope stability analysis is conducted to determine the stability of the lowwall slope based on the design produced in March and June. The lowwall slope stability analysis will also be carried out until the excavation of the mining floor is continued up to RL -20 and RL -50. Slope stability analysis is carried out using the limit equilibrium method for circular failure and plane failure using the help of Rocscience Slide 6.0 software. In the limit equilibrium method, slope safety factors are stated by the number of safety factor (sf). Slopes are modeled through AutoCAD software first, and the lithology of slope modeled through the correlation of material stratigraphy. Models that have not fulfilled safe conditions with SF <1.3 (according to the Kepmen ESDM No. 1827 K / 30 / MEM 2018) are remodeled with different geometry to produce SF values that meet safe conditions. This geometry will be given as recommendation for slope geometry for PT XYZ. Simulation results show that of the four (4) slope models analyzed, three (3) of them are June, RL -20, and RL-50 models show unsafe conditions. The June model shows that SF in critical condition with SF = 1.1 dropped significantly compared to the model in March with the minimum SF = 1.4. This dropped SF can be indicate how the tension cracks is formed. Geometry changes are done by reducing the overall slope, reducing the height of a single slope and increasing the width of the berm. Recommended slope geometry produces safe conditions with SF> 1.3.